Religião e saúde: relações entre a Umbanda e a Medicina nas práticas de cura - Vale, Johnatan Ferreira Marques do (2013)
This work aims to describe and analyse the healing practices in umbanda and the relations that are established with the medical ones. The description and analysis of healing practices used in umbanda might not be apart from the analysis of its relation with the official therapies, as the religious system categorizes the illnesses which belong to the spirit and the ones are related to medicine (material ones), which denotes a practical and symbolical practice in therapy areas. Every single cure practice effectively done in the umbanda area is set in an illness categorization, referring necessarily to the official Medicine, establishing a dialogue, an argument and a tension with a legitimate sphere of treatment. At the same time which the treatable diseases are equally divided, religious therapy invades the space of medicine when it affirms to treat even the material illnesses. At this moment, it mentions its advantages as therapy, overestimating its know-how facing medical practices’ frailties and limitations. This study aimed to give sense to this conflict, examining questions that face the reality, such as: how the umbandistas, as members of popular classes, are integrated to public health system? Which complaints do they present referring to the medical practice? Does it coexist with its experience in the illness process and its representations? How the religious agency accomplishes its therapy function? Can it be designed as a compensatory medicine to the lack of health? During the research, it was possible to notice that umbanda practicioners while users of SUS (Sistema Único de Saúde) evaluate negatively the public health system. If it was only possible to evaluate their complaints about it, conceived as not working and deficient, it could be possible to observe their questions and views about the medical practice, which is defined by them as ‘authoritarian’, ‘restrictive’ and ‘full of medicines’ e pay attention to their reservations to treatment institutions (hospitals), that were conceived not as a place of care, but as a space which could damage their people’s health seriously and even kill. The criticisms and complaints which were made to the oficial treatment system show that umbanda practicioners do not feel that they are inserted in a satisfactory way in SUS context, that make them to reject the use of these services. As long as they criticize and complain, the places where umbanda happen (terreiros) do their therapy and assistance function showing clearly that umbanda in João Pessoa do their job as a refugee, offering treatments which are lined in charity and attention to the person himself/herself. It made me to define it as a compensatory medicine to remedy the lack of a health system. Aiming to answer to these answers, this research was methodologically oriented to a qualitative approach and two techniques of research were used: some semi-structured interviews with nine Babalorixás and five Ialorixás, whose ages were between 28 and 77 years old, and also the participant observation applied to the context of jurema de chão, jurema batida and orixás’ rituals, these ceremonies were realized weekly in the umbanda’s places in João Pessoa. It was theoretically based in a knowledge interface, through the Body’s and Health’s Anthropology, AfroBrazilian Religion Anthropology, or Medicine and Illness’ Sociology. To look for a multidisciplinary and theoretical matrix succeeds from the complexity of the object of this research and the difficulty of stablishing over it some studies, approximations and classifications.